Fat Hounsfield Unit Reference Interval Derived through an Indirect Method - Marian Pop; Marius Mărușteri (Diagnostics, 2023)
Background: In vivo Hounsfield Unit (HU) values have traditionally been determined using direct CT image measurements. These measurements are dependent on the window/level used to examine the CT image and the individual conducting the fat tissue tracing. Methods: Using an indirect method, a new reference interval (RI) is proposed. A total of 4000 samples of fat tissues were collected from routine abdominal CT examinations. A linear regression equation was then calculated using the linear part of the cumulative frequency plot of their average values. Results: The regression function for total abdominal fat was determined to be y = 35.376*x − 123.48, and a 95% confidence RI of −123 to −89 was computed. A significant difference of 3.82 was observed between the average fat HU values of visceral and subcutaneous areas. Conclusions: Using statistical methods and the in vivo measurements of patient data, a series of RIs were determined for fat HU that is consistent with theoretical values.